2018
DOI: 10.1111/jphp.13041
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II prevents hypertensive heart disease by alleviating endoplasmic reticulum stress via the PERK/ATF-4/CHOP signalling pathway in spontaneously hypertensive rats

Abstract: Objectives Reducing endoplasmic reticulum stress (ERS)‐induced cardiomyocyte apoptosis is a key strategy for preventing hypertensive heart disease. In our previous study, Icariside II can improve left ventricular remodelling in spontaneously hypertensive rats (SHRs). This study aims to determine whether Icariside II can exert its effect by inhibiting ERS‐induced cardiomyocyte apoptosis via the PERK/ATF‐4/CHOP signalling pathway. Methods Spontaneously hypertensive rats were randomly divided into model group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Therefore, a rapid up-regulation of GRP78 is considered as the most sensitive marker of ER stress. CCAAT/enhancer binding protein homologous protein (CHOP) is an important signaling molecule for pro-apoptosis, and ER stress-specific transcription factor, which has a low expression under normal conditions but a high expression under ER stress [9]. Thus, CHOP is considered as a marker of ER stress.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a rapid up-regulation of GRP78 is considered as the most sensitive marker of ER stress. CCAAT/enhancer binding protein homologous protein (CHOP) is an important signaling molecule for pro-apoptosis, and ER stress-specific transcription factor, which has a low expression under normal conditions but a high expression under ER stress [9]. Thus, CHOP is considered as a marker of ER stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the decrease in EF and FS indicates that spontaneously hypertensive rats (SHRs) exhibited ventricular remodeling and dysfunction [ 8 ]. In this study, we established an HFD-induced HHD rat model according to the previous report [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The left ventricle function was measured as described [ 8 ] at the end of the experiment. Briefly, the rats were fixed on an animal operation platform after anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found Icariside II alleviated hypertension-mediated cardiomyocyte apoptosis and prevented the decline in cardiac function in the rats. Icariside II reduced the expression of GRP78, CHOP, PERK, and ATF4 at both the protein and mRNA level to alleviate the extent of ER stress, reducing the percentage of apoptotic cells ( Wu et al, 2019b ). Icariside II has also been implemented in autophagy.…”
Section: Endoplasmic Reticulum Stress Responsementioning
confidence: 99%